Innovative Research Approaches to Cope with Water Security in Africa. (6th October 2020) - de Miguel, Angel; Froebrich, Jochen; Jaouani, Atef; Souissi, Yasmine; Elmahdi, Amgad; Mateo‐Sagasta, Javier; Al‐Hamdi, Mohamed; Frascari, Dario
ABSTRACT: To achieve a water‐secure world, water management should be approached from a multidimensional and integrative perspective, addressing the water‐related issues of health, household supply, economics, the environment, and resilience to water‐related and climate change hazards. Although water security has significantly improved since 2000 in Africa, there are still vast inequalities in access to water suitable in terms of quantity and quality, especially in rural areas. To achieve water‐related sustainable development of African economies, a broad scope of innovative technological and management solutions is required, involving governments, research institutions, private sector parties, and civil society. This special series, composed of 8 papers, illustrates a selection of the most relevant results achieved by the 7 research projects selected and financed by the European Union under 2 dedicated Horizon 2020 calls in 2015: Water‐5b‐2015 "A coordination platform" and Water‐5c‐2015 "Development of water supply and sanitation technology, systems and tools, and/or methodologies." The innovations presented in this special series include both technological advancements and w'ater management approaches, given that the development of water‐related technologies in developing countries needs to be integrated into water management strategies and economic instruments. This special series aims to help policy makers take informed decisions on how to implement innovative approaches to increase water security in African countries. Integr Environ Assess Manag 2020;16:853–855. © 2020 The Authors. Integrated Environmental Assessment and Management published by Wiley Periodicals LLC on behalf of Society of Environmental Toxicology & Chemistry (SETAC) KEY POINTS: To achieve a more water secure world, water management should be approached from a multidimensional and integrative perspective. This special series aims to help policy makers take informed decisions on how to implement innovative approaches to increase water security in African countries.